Effect of geometry on the compression characteristics of bonded brickwork. (August 2021) - Zahra, Tatheer; Asad, Mohammad; Thamboo, Julian
Abstract: Bonded brickwork walls of large thickness constructed with double or triple bricks are common in loadbearing historical masonry structures in many regions which require interventions and compression capacity evaluation. However, current design provisions for compression capacity prediction are primarily based on single brick prisms and wallette specimens. Due to anisotropic nature of masonry, the strength and deformation characteristics of bonded brickwork with double and triple brick thicknesses are different to the single leaf brickwork; and their design using the provisions of single leaf bonded brickwork specimens may be un-conservative. To expand the knowledge on the compressive behaviour of bonded brickwork, a detailed numerical investigation has been reported in this paper. A simplified Finite element (FE) based micro-modelling technique was implemented to simulate the compression response of bonded brickwork specimens. The developed FE modelling technique was initially verified against the experimental predictions of compressive capacities and axial stress-strain curves. The numerical modelling results iterated that there was no noticeable increase in the compressive capacity of the masonry with increase in the brickwork thicknesses due to increased number of weak head joints. The validated models were then employed to study the effect of slenderness of the bonded brickwork specimens on the axial compression response. The height to thickness (slenderness) ratios of the bonded brickwork were varied from 1.4 to 10.9 for analysing 30 different cases with two brick strengths. Results showed that with increasing slenderness ratio, the compressive strength of the bonded brickwork reduces for all bonded thicknesses. The parametric study indicates that the slenderness ratio influences the compression characteristics of bonded brickwork specimens; subsequently, correction factors for the compressive strengths determined with different slenderness ratios of brickwork specimens are proposed.